Fairytale Semantic Differential Technique: Diagnostic Possibilities - Petrenko V.F; Mitina O.V (Moscow State University of Psychology and Education, 2019)
The method "Fairy Semantic Differential", during which a respondent should assess a number of fairy-tale characters according to a set of personal characteristics, is designed for the individual work of a psychologist with children 4-10 years old.Personality characteristics, according to which the characters are evaluated, are formulated by words that adults use when dealing with children of this age.An analysis of the child's attitude to characters allows us to determine the specificity of his/her moral-value sphere.Quantitative indicators that can be calculated using the data of the answering the questionnaire are discussed.These indicators characterize the child's attitudes toward oneself and others, dimension of categorial space of interpersonal perception, content and hierarchy of these categories, the level of cognitive development in this area, the degree of socialization.The results of an empirical study are presented.Age/sex differences in the cognitive complexity of interpersonal perception and socialization were shown.For each indicator normative intervals are calculated.Examples of individual semantic space are presented.